ANALISIS PENERAPAN METODE DISKUSI DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA SD MUHAMMADIYAH 3 LIMBOTO KABUPATEN GORONTALO - Minggulian Tebai; Yane Hardiyanti Mahmud; Suleman Suleman (Jurnal Ilmu Pendidikan UMGo, 2025)
This study aims to analyze the implementation of the discussion method in Indonesian language learning at SD Muhammadiyah 3 Limboto, Gorontalo Regency. The study was motivated by the need to create more active, communicative, and student-centered Indonesian language learning, particularly in developing students’ speaking, listening, critical thinking, and collaborative skills. This research employed a qualitative descriptive approach. Data were collected through classroom observation, interviews with the principal, teachers, and students, questionnaires, and documentation. The data were analyzed through data reduction, data display, thematic categorization, and conclusion drawing. The findings show that the discussion method can support Indonesian language learning when teachers prepare clear objectives, select relevant topics, provide guiding questions, organize groups, facilitate equitable participation, manage discussion time, and close the activity with reflection and feedback. The discussion method encourages students to express opinions, listen to peers, respect different perspectives, and construct meaning through social interaction. However, several challenges remain, including students’ shyness, unequal participation, limited vocabulary, and classroom management issues. Therefore, the discussion method needs to be implemented through systematic planning, teacher facilitation, and consistent reinforcement. The study concludes that the discussion method is a relevant instructional strategy for strengthening communication skills and meaningful learning in elementary Indonesian language classrooms.